E-Commerce Website as Seller Media for End User at Banyuwangi Mall - Puji Dwi Astuti, Pending; A. Gde Satia Utama, A (International Journal of Engineering and Technology, 2018)
This study aims to perform evaluation using End User Computing Satisfaction theory on Seller Account Banyuwangi Mall. The approach used in this research is qualitative explorative approach with case study method from SME seller of goods product. The data collection procedure used in this research is interview, observation, and documentation. The result of this research based on evaluation of Banyuwangi Mall e-commerce system shows have satisfaction as end user. The current system is adequate, but needs to be improved. Such improvements are used to improve the efficient use of the Banyuwangi Mall ecommerce system, especially the seller account system operated by SME actors who sell their products through Banyuwangi Mall. The improvement is a redesign of the sales system. The designs made have been adjusted based on the necessary improvements taking into consideration the costs and benefits, as well as the internal controls in each of their activities, so that the design proposal on the Banyuwangi Mall seller account is well worth considering. Further research is expected to be an evaluation and improvement of the appearance of the customer or buyer to make buyers more interested in transactions through Banyuwangi Mall and simplify the use.Â Â